Mutualist-Provisioned Resources Impact Vector Competency - Rita V. M. Rio (American Society for Microbiology, 2019)
ABSTRACT Many symbionts supplement their host’s diet with essential nutrients. However, whether these nutrients also enhance parasitism is unknown. In this study, we investigated whether folate (vitamin B9) production by the tsetse fly (Glossina spp.) essential mutualist, Wigglesworthia, aids auxotrophic African trypanosomes in completing their life cycle within this obligate vector. We show that the expression of Wigglesworthia folate biosynthesis genes changes with the progression of trypanosome infection within tsetse. The disruption of Wigglesworthia folate production caused a reduction in the percentage of flies that housed midgut (MG) trypanosome infections. However, decreased folate did not prevent MG trypanosomes from migrating to and establishing an infection in the fly’s salivary glands, thus suggesting that nutrient requirements vary throughout the trypanosome life cycle. We further substantiated that trypanosomes rely on symbiont-generated folate by feeding this vitamin to Glossina brevipalpis, which exhibits low trypanosome vector competency and houses Wigglesworthia incapable of producing folate. Folate-supplemented G. brevipalpis flies were significantly more susceptible to trypanosome infection, further demonstrating that this vitamin facilitates parasite infection establishment. Our cumulative results provide evidence that Wigglesworthia provides a key metabolite (folate) that is “hijacked” by trypanosomes to enhance their infectivity, thus indirectly impacting tsetse species vector competency. Parasite dependence on symbiont-derived micronutrients, which likely also occurs in other arthropod vectors, represents a relationship that may be exploited to reduce disease transmission. IMPORTANCE Parasites elicit several physiological changes in their host to enhance transmission. Little is known about the functional association between parasitism and microbiota-provisioned resources typically dedicated to animal hosts and how these goods may be rerouted to optimize parasite development. This study is the first to identify a specific symbiont-generated metabolite that impacts insect vector competence by facilitating parasite establishment and, thus, eventual transmission. Specifically, we demonstrate that the tsetse fly obligate mutualist Wigglesworthia provisions folate (vitamin B9) that pathogenic African trypanosomes exploit in an effort to successfully establish an infection in the vector’s MG. This process is essential for the parasite to complete its life cycle and be transmitted to a new vertebrate host. Disrupting metabolic contributions provided by the microbiota of arthropod disease vectors may fuel future innovative control strategies while also offering minimal nontarget effects.